Ross procedure is a safe treatment option for aortic valve endocarditis: Long-term follow-up of 42 patients. (15th January 2016) - Ringle, A.; Richardson, M.; Juthier, F.; Rousse, N.; Polge, A.S.; Coisne, A.; Duva-Pentiah, A.; Abda, A. Ben; Banfi, C.; Montaigne, D.; Vincentelli, A.; Prat, A.
Abstract: Background: Aortic root replacement with a pulmonary autograft (Ross procedure) can be performed as a treatment of aortic valve endocarditis, avoiding prosthetic valve implantation in septic context. We sought to assess long-term outcomes of the Ross procedure in this indication. Methods: From April 1992 to March 2009, the intervention was performed in 42 patients (mean age 34 ± 8 years) suffering from an active or ancient aortic valve endocarditis. 36% of the patients had extensive perivalvular involvement, and surgery was urgent in 18 patients (43%). We performed a prospective clinical and echocardiographic follow-up of this population. Results: Median follow-up was 10 years (4–21 years). Overall survival at 10 and 15 years was respectively 87 ± 5% and 81 ± 8%. Perioperative mortality was 4.7% (2 patients) and no late cardiac death was reported. Eight patients (19%) underwent repeat surgery for autograft and/or homograft dysfunction at a median time of 8.4 years (3 months–18 years). Rate of recurrent endocarditis was low (7%—3 patients), including 1 in a context of persistent intravenous drug abuse. Clinical follow-up showed good functional status for all patients with NYHA ≤ II, and less than 25% of patients requiring cardiovascular medication. Late echocardiographic follow-up demonstrated well-functioning autograft and homograft, with only one severe aortic regurgitation, and one significant increase in pulmonary mean gradient. Conclusion: The Ross procedure in aortic valve endocarditis is an interesting alternative to prosthetic valvular replacement in a selected population, with a high rate of survival free from any cardiovascular event or medication requirement.